Comparison of injuries among motorcycle, moped and bicycle traffic accident victims. (2nd January 2022) - Kent, Tyler; Miller, Jordan; Shreve, Colby; Allenback, Gayle; Wentz, Brock
ABSTRACT: Objective: Motorcycles, moped scooters and bicycles are commonly involved in traffic accidents and riders often suffer significant morbidity and mortality. The aim of this study is to compare and categorize the different injury patterns and fractures suffered by riders of each vehicle type after a traffic accident. Methods: Data from a level 1 trauma center in Las Vegas, Nevada were analyzed. Traffic accident victims riding a motorcycle, moped, or bicycle from 2013 to 2017 were included. Injury location and fracture location were assigned to six and sixteen categorical locations, respectively. Descriptive statistics, including frequency counts for categorical data and mean for continuous data, were calculated for the full sample and for each of the vehicle types. Logistic regression was performed on race, categorized age, vehicle type and helmet use to calculate adjusted odds ratios for injury type between the three groups. Results: Of the 2115 patients, 1372 were motorcyclists, 356 were moped scooter riders and 387 were bicyclists. Overall the vast majority of injuries reported were of the extremities or pelvic girdle (62.2%), and this was true regardless of vehicle type. Head and neck injuries were significantly more common in bicyclists (39.5%) and moped riders (34.6%), than in motorcyclists (22.7%). Helmet use was substantially lower in the moped (34%) and bicycle (20%) groups compared to the motorcycle group (85%). The most common fractures regardless of vehicle type were of the skull/face, rib, vertebral, and tibia/fibula with slight variations between vehicle groups. Conclusion: Similarities were seen in the most common fracture and injury patterns between the three groups. Head and neck injuries were much more common in moped and bicycle riders compared to motorcyclists. This is most likely due to the significantly higher percentage of motorcycle riders who wore a helmet. Counseling regarding helmet and protective equipment use, especially among moped and bicycle riders is essential to reduce head injuries.